New loci for body fat percentage reveal link between adiposity and cardiometabolic disease risk - Yingchang Lu (Nature Portfolio, 2016)
A genome-wide association meta-analysis study here shows novel genetic loci to be associated to body fat percentage, and describes cross-phenotype association that further demonstrate a close relationship between adiposity and cardiovascular disease risk.